The isolation and characterisation of secondary metabolites from selected South African marine red algae (Rhodophyta) - Fakee, Jameel (Rhodes University, Faculty of Pharmacy, Pharmacy, 2013)
Secondary metabolites from natural sources are fast growing as popular drug leads. The structural novelty and favourable biological activity that these compounds display contribute to their popularity as drugs of the future. Examples of such compounds include the potent anticancer drug paclitaxel isolated from the bark of a yew tree as well as the more commonly known analgesic aspirin which stems from the bark of the willow tree. The biological activities exhibited by these secondary metabolites are vast and range from antimicrobial to anticancer activity to mention but a few. As a result, the isolation of novel compounds from natural sources is on the rise. The South African seaboard is home to a wealth of various marine algal species which produce fascinating secondary metabolites. For example, Portierria hornemanii was shown to produce halomon, a halogenated monoterpene which has displayed promising cytotoxic activity. This study thus focused primarily on pursuing novel compounds from three endemic South African marine algal species which have never been analysed previously from a chemical perspective. These are Plocamium rigidum (Bory de Saint-Vincent), Laurencia natalensis (Kylin) and Delisea flaccida (Suhr) Papenfuss. Four known compounds and one new halogenated monoterpene, (2E,5E,7Z)-8-chloro- 7-(dichloromethyl)-4-hydroxy-3-methylocta-2,5,7-trienal, were isolated from Plocamium rigidum. The breast cancer (MCF-7 cell line) inhibitory activity for these compounds was assessed and it was observed that an increase in the lipophilic nature of the compounds produced more favourable IC50 values. A pre-cursor to bromofucin type compounds, cis-laurencenyne, was isolated from Laurencia natalensis, as well as a new acetoxy chamigrane type compound, 4-bromo- 3,10-dichloro-7-hydroxy-3,7,11,11-tetramethylspiro [6.6] undec-1-yl acetate. Delisea flaccida was seen to contain two known bromofuranone type compounds isolated as an isomeric mixture, 1-[(5Z)-4-bromo-5-(bromomethylidene)-2-oxo-2,5- dihydrofuran-3-yl] butyl acetate and 1-[(5E)-4-bromo-5-(bromomethylidene)-2- oxo-2,5-dihydrofuran-3-yl]butyl acetate. These compounds are famous for their ability to inhibit bacterial biofilm production and they have been isolated before from an Australian Delisea spp,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Metabolites Marine algae -- South Africa; Marine algae -- Therapeutic use; Metabolites -- Therapeutic use; Marine metabolites; Plocamocera; Red algae; Laurencia; Delisea flaccida